Post-prostatectomy Stricture Clinical Evaluation and Management - Bilal, H. (Journal of Postgraduate Medical Institute, 2011)
Seven cases of Urethral Stricturing are discussed in this article with emphasis on clinical, radiological and endoscopic evaluation. It is suggested that the physio-pathological basis of the disease lends itself to certain clinical syndromes in respect of benign prostatic fibroadenomatous disease, which itself clearly demarcates the parameters of definitive surgical treatment. The author believes that the preventive measures largely originate from rational understanding of the whole mechanism and the objective of the exercise is the prevention of these strictures